The Effect Of Communicative Language Teaching On Students Speaking Skill - Euis Yanah Mulyanah; Ishak Ishak; Ratih Kusuma Dewi (UNIVERSITAS RAHARJA, 2018)
The aims of this research were to find out whether there are good response and improvement of students’ speaking skill between before and after being taught through Communicative Language Teaching (CLT). The samples of this research were the VIII A and VIII B class of the Eighth Grade of SMP Negeri 21 Tangerang in academic year 2015/2016. The researcher used non-equivalent control group design. The instrument was oral test. The result of the research showed that there was improvement of the students’ speaking skill in actively communicative by using CLT. The result of t-test showed that t was bigger than ttable. The result of tcount was 4.2105 and ttable was 2.0021. It means that the researcher’s hypothesis (H1), there is significant difference of post-test scores between experiment class and control class is accepted. The average score of pre-test in experiment class is 67.33 while the average score of pre-test in control class is 66.50. The average of the post-test score in experiment class was 83.00 while the average of the post-test score in control class was 75.00. It showed that CLT can improve the students’ speaking skill.